An inland waterway freight service in comparison to land-based alternatives in South-Eastern Europe: energy efficiency and air quality performance - Tzannatos, Ernestos; Tselentis, Basil; Corres, Alkis (Transport, 2016)
Towards the strive of developing sustainable freight transport networks in Europe, the EU and the developing South-Eastern Europe in particular, this paper initially examines the feasibility of establishing a navigable link along the Axios–Morava waterway, for freight transport between the Eastern Mediterranean Sea (via the Aegean) and the Danube River, and then proceeds with its energy and air quality comparison with the competing modes of rail and road. It was found that this waterway service is technically feasible and offers an energy and carbon efficient alternative to road-borne and rail-borne freight. However, the land-based services were found to be superior with regard to their impact upon the air quality of the region, mainly attributed to the stricter emission standards applicable to these transport modes. Finally, it is proposed to build on the ongoing international policy and funding interest in this project in order to implement all the necessary infrastructural and operational changes which will make the proposed waterway service a commercially and environmentally sustainable freight transport alternative in South-Eastern Europe.